Isolated metachronous splenic metastasis from renal cell carcinoma after 5 years. (14th December 2012) - Nunes, Thiago Franchi; Szejnfeld, Denis; Miiji, Luciana Nakao Odashiro; Goldman, Suzan Menasce
Abstract : Primary and metastatic tumours of the spleen are uncommon. The incidence of isolated metastasis from other organs is less than 1%. We report the case of a 55-year-old woman with clear cell carcinoma of the kidney, who underwent radical nephrectomy. After a 5-year follow-up period, a hypervascular nodule was detected in the spleen on MRI. Six months later, control MRI showed that its appearance had changed to a hypervascular mass with areas of central necrosis. A splenectomy was performed and histopathological examination of the spleen confirmed the presence of clear cell carcinoma with infiltration of the capsule. This is only the seventh case described in the literature of isolated splenic metastasis from clear cell carcinoma and the first such case containing MRI.